BUSINESS RISK AND RETURN CONCEPT IN ISLAMIC INVESTMENT - Kadir, Syahruddin; Musdiana, Andi Desy (jfpublisher, 2024)
In making investments, one must consider risk and return before committing capital. Avoiding unpredictable risks or those that could endanger economic and social sustainability is crucial. This study aims to analyze the concept and relationship between business risk and return on Islamic investment. The main issues addressed include how Sharia principles influence the risk and return profile of investments, as well as the challenges in measuring and managing risk within the Islamic finance framework. The research employs a qualitative descriptive analysis of secondary sources (journal articles). The findings indicate that Islamic investments have distinct risk and return characteristics compared to conventional investments. They emphasize risk-sharing, the prohibition of usury (riba), and a focus on real assets, which tend to produce a more stable risk-return profile in the medium and long term. Challenges include the standardization of risk measurement and the lack of diversification in some Islamic financial instruments, necessitating further innovation in product development and risk management in alignment with Sharia principles.